Effect of fine aggregate angularity on rutting resistance of asphalt concrete AC10 - Ramli, Izzul (2013)
Fine Aggregate Angularity (FAA) has been identified as one of the important aggregate properties contributing to the stability of Hot Mix Asphalt (HMA)and its resistance against permanent deformation such as rutting.The performance of dense graded asphalt mixture is significantly influenced by the shape, angularity and surface texture of fine aggregates. This study determines the FAAfor different types of aggregates namely granite and natural sand andevaluates the rutting resistance of AC 10 mixture added with the aforementioned aggregates. Besides the FAA test, other tests that were carried out include Marshall test and wheel tracking test for measuring the rutting resistance. Marshall Procedures were undertaken to obtain the stiffness, stability, density, flow, VTM and VFB. It was found that Marshall properties for mixture added with crushed aggregate are higher than mixture with natural sand in terms of Stability, Stiffness, and Flow. The result shows that mixture with crushed granite has higher percentage of FAA (46%)compared to the one with natural sand (37%).From wheel tracking test, it was observed that the rut depth for specimen with crushed granite is higher compared to specimen with natural sand.Therefore it can be concluded that fine aggregates with more angular shape, increase the rutting resistance.